Professional formation of women as a factor of its self-esteem - Odintsova, V. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
In the given article are discussed the impact of professional development on self-esteem women, and the various approaches to the definition of "career", the typology of the foreign and domestic authors. In the article were presented the results of investigations of the influence of the type of career on the self-esteem of women.